background image

18.3. CONVERGENCE OF JOIN

277

18.2. Relationships between convergence and continuity

Lemma

1457

.

Let

µ

,

ν

be endofuncoids,

f

FCD

(Ob

µ,

Ob

ν

),

A ∈

F

(Ob

µ

),

Src

f

= Ob

µ

, Dst

f

= Ob

ν

. If

f

C(

µ

|

A

, ν

) then

f

|

h

µ

iA

ν

→ h

f

iA ⇔ h

f

µ

|

A

iA v h

ν

f

iA

.

Proof.

f

|

h

µ

iA

ν

→ h

f

iA ⇔

im

f

|

h

µ

iA

v h

ν

ih

f

iA ⇔

h

f

ih

µ

iA v h

ν

ih

f

iA ⇔ h

f

µ

iA v h

ν

f

iA ⇔ h

f

µ

|

A

iA v h

ν

f

iA

.

Theorem

1458

.

Let

µ

,

ν

be endofuncoids,

f

FCD

(Ob

µ,

Ob

ν

),

A ∈

F

(Ob

µ

), Src

f

= Ob

µ

, Dst

f

= Ob

ν

. If

f

C(

µ

|

A

, ν

) then

f

|

h

µ

iA

ν

→ h

f

iA

.

Proof.

f

|

h

µ

iA

ν

→ h

f

iA ⇔

(by the lemma)

⇔ h

f

µ

|

A

iA v h

ν

f

iA ⇐

f

µ

|

A

v

ν

f

f

C(

µ

|

A

, ν

)

.

Corollary

1459

.

Let

µ

,

ν

be endofuncoids,

f

FCD

(Ob

µ,

Ob

ν

),

A ∈

F

(Ob

µ

), Src

f

= Ob

µ

, Dst

f

= Ob

ν

. If

f

C(

µ, ν

) then

f

|

h

µ

iA

ν

→ h

f

iA

.

Theorem

1460

.

Let

µ

,

ν

be endofuncoids,

f

FCD

(Ob

µ,

Ob

ν

),

A ∈

F

(Ob

µ

)

be an ultrafilter, Src

f

= Ob

µ

, Dst

f

= Ob

ν

.

f

C(

µ

|

A

, ν

) iff

f

|

h

µ

iA

ν

→ h

f

iA

.

Proof.

f

|

h

µ

iA

ν

→ h

f

iA ⇔

(by the lemma)

⇔ h

f

µ

|

A

iA v h

ν

f

iA ⇔

(used the fact that

A

is an ultrafilter)

f

µ

|

A

v

ν

f

|

A

f

µ

|

A

v

ν

f

f

C(

µ

|

A

, ν

)

.

18.3. Convergence of join

Proposition

1461

.

d

S

µ

→ A ⇔ ∀F ∈

S

:

F

µ

→ A

for every collection

S

of

filters on Dst

µ

and filter

A

on Src

µ

, for every funcoid

µ

.

Proof.

l

S

µ

→ A ⇔

l

S

v h

µ

iA ⇔ ∀F ∈

S

:

F v h

µ

iA ⇔ ∀F ∈

S

:

F

µ

→ A

.

Corollary

1462

.

d

F

µ

→ A ⇔ ∀

f

F

:

f

µ

→ A

for every collection

F

of

funcoids

f

such that Dst

f

= Dst

µ

and filter

A

on Src

µ

, for every funcoid

µ

.

Proof.

By corollary

893

we have

l

F

µ

→ A ⇔

im

l

F

µ

→ A ⇔

l

h

im

i

F

µ

→ A ⇔

f

∈ h

im

i

F

:

F

µ

→ A ⇔ ∀

f

F

: im

f

µ

→ A ⇔ ∀

f

F

:

f

µ

→ A

.

Theorem

1463

.

f

|

B

0

tB

1

µ

→ A ⇔

f

|

B

0

µ

→ A ∧

f

|

B

1

µ

→ A

. for all filters

A

,

B

0

,

B

1

and funcoids

µ

,

f

and

g

on suitable sets.

Proof.

As easily follows from distributivity of the lattices of funcoids we have

f

|

B

0

tB

1

=

f

|

B

0

t

f

|

B

1

. Thus our theorem follows from the previous corollary.